Food Addiction, Saturated Fat Intake, and Body Mass Index in Peruvian Adults: A Cross-Sectional Survey - Dulce E. Lopez-Lopez; Ivett K. Saavedra-Roman; Yaquelin E. Calizaya-Milla; Jacksaint Saintila (Journal of Nutrition and Metabolism)
Background. Cardiovascular diseases (CVDs) constitute one of the main public health problems and represent a greater risk of mortality and morbidity for the world population. The objective of the study was to determine food addiction, saturated fat intake, and body mass index (BMI) in Peruvian adults. Materials and Methods. A cross-sectional online survey was applied to 394 Peruvian adults over 18 years old residing in the three regions of the country. Participant data was collected through a prestructured online electronic survey. Food addiction was assessed using the Yale Food Addiction Scale self-administered questionnaire. A validated food frequency questionnaire was used to measure saturated fat intake. Finally, the sociodemographic and anthropometric variables were collected through a registration form. Results. There were no significant differences in food addiction between men and women (p<0.05). More than half of the participants who presented food addiction are overweight (54.1%, p<0.001). The highest proportion of those who had a high intake of saturated fat had a food addiction (62.6%, p<0.001). The highest percentage of men who were overweight was higher compared to women (49.7% vs. 38.4%, p<0.05). Conclusion. The findings of this study suggest that addictive eating behaviors and high saturated fat intake should be considered as part of efforts to prevent problems related to eating, obesity, and CVD.